First-principles studies on optical absorption of [010] screw dislocation in KDP crystals. Issue 42 (7th October 2021) - Jiang, Xuanyu; Li, Yang; Wei, Liening; Xu, Mingxia; Zhang, Lisong; Chen, Jun; Sun, Xun
Abstract : The stress caused by the [010] dislocation in KDP deforms the crystal structure, introduces extra optical absorption and narrows the band gap. Abstract : The structure, total system energies, electronic structures and optical absorption of the [010] screw dislocation in potassium dihydrogen phosphate (KH2 PO4, KDP) crystals are investigated in the framework of the density functional theory with the HSE06 functional. To describe the complete stress field, six supercells under different shear stress caused by the [010] dislocation are constructed. The results have confirmed that the shear stress will deform the crystal structure and narrow the band gap. One of the more significant findings to emerge from this study is that when the crystal is under a large shear stress, in other words, in the vicinity of the dislocation core the dehydration will occur and it will enhance the linear and nonlinear absorption of the KDP crystal. The H atom and hydroxyl are contributed by different PO4 tetrahedra, respectively. The data reported here appear to support the assumption that the [010] dislocation has a harmful influence on the resistance of KDP to the laser irradiation. In spite of its limitations, these findings have significant implications to understand how to improve LIDT of the KDP crystal and have a number of important implications for future practice.